Pregnancy and neonatal outcomes of COVID‐19: coreporting of common outcomes from PAN‐COVID and AAP‐SONPM registries. (1st April 2021) - Mullins, E.; Hudak, M. L.; Banerjee, J.; Getzlaff, T.; Townson, J.; Barnette, K.; Playle, R.; Perry, A.; Bourne, T.; Lees, C. C.; ,
ABSTRACT: Objective: Few large cohort studies have reported data on maternal, fetal, perinatal and neonatal outcomes associated with severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection in pregnancy. We report the outcome of infected pregnancies from a collaboration formed early during the pandemic between the investigators of two registries, the UK and Global Pregnancy and Neonatal outcomes in COVID‐19 (PAN‐COVID) study and the American Academy of Pediatrics (AAP) Section on Neonatal–Perinatal Medicine (SONPM) National Perinatal COVID‐19 Registry. Methods: This was an analysis of data from the PAN‐COVID registry (1 January to 25 July 2020), which includes pregnancies with suspected or confirmed maternal SARS‐CoV‐2 infection at any stage in pregnancy, and the AAP‐SONPM National Perinatal COVID‐19 registry (4 April to 8 August 2020), which includes pregnancies with positive maternal testing for SARS‐CoV‐2 from 14 days before delivery to 3 days after delivery. The registries collected data on maternal, fetal, perinatal and neonatal outcomes. The PAN‐COVID results are presented overall for pregnancies with suspected or confirmed SARS‐CoV‐2 infection and separately in those with confirmed infection. Results: We report on 4005 pregnant women with suspected or confirmed SARS‐CoV‐2 infection (1606 from PAN‐COVID and 2399 from AAP‐SONPM). For obstetric outcomes, in PAN‐COVID overall and in those with confirmed infection in PAN‐COVID and AAP‐SONPM, respectively, maternal death occurred in 0.5%, 0.5% and 0.2% of cases, early neonatal death in 0.2%, 0.3% and 0.3% of cases and stillbirth in 0.5%, 0.6% and 0.4% of cases. Delivery was preterm (< 37 weeks' gestation) in 12.0% of all women in PAN‐COVID, in 16.1% of those women with confirmed infection in PAN‐COVID and in 15.7% of women in AAP‐SONPM. Extreme preterm delivery (< 27 weeks' gestation) occurred in 0.5% of cases in PAN‐COVID and 0.3% in AAP‐SONPM. Neonatal SARS‐CoV‐2 infection was reported in 0.9% of all deliveries in PAN‐COVID overall, in 2.0% in those with confirmed infection in PAN‐COVID and in 1.8% in AAP‐SONPM; the proportions of neonates tested were 9.5%, 20.7% and 87.2%, respectively. The rates of a small‐for‐gestational‐age (SGA) neonate were 8.2% in PAN‐COVID overall, 9.7% in those with confirmed infection and 9.6% in AAP‐SONPM. Mean gestational‐age‐adjusted birth‐weight Z ‐scores were −0.03 in PAN‐COVID and −0.18 in AAP‐SONPM. Conclusions: The findings from the UK and USA registries of pregnancies with SARS‐CoV‐2 infection were remarkably concordant. Preterm delivery affected a higher proportion of women than expected based on historical and contemporaneous national data. The proportions of pregnancies affected by stillbirth, a SGA infant or early neonatal death were comparable to those in historical and contemporaneous UK and USA data. Although maternal death was uncommon, the rate was higher than expected based on UK and USA population data, which is likely explained by underascertainment of women affected by milder or asymptomatic infection in pregnancy in the PAN‐COVID study, although not in the AAP‐SONPM study. The data presented support strong guidance for enhanced precautions to prevent SARS‐CoV‐2 infection in pregnancy, particularly in the context of increased risks of preterm delivery and maternal mortality, and for priority vaccination of pregnant women and women planning pregnancy. Copyright © 2021 ISUOG. Published by John Wiley & Sons Ltd. Abstract : This article's abstract has been translated into Spanish and Chinese. Follow the links from the abstract to view the translations. RESUMEN: Resultados del embarazo y neonatales de COVID‐19: informe conjunto de resultados comunes de los registros PAN‐COVID y AAP‐SONPM Objetivo: Pocos estudios de cohortes grandes han publicado datos sobre los resultados maternos, fetales, perinatales y neonatales asociados a la infección por el coronavirus del síndrome respiratorio agudo severo 2 (SRAS‐CoV‐2) en el embarazo. Este estudio informa de los resultados de los embarazos con infección a partir de una colaboración formada a principios de la pandemia entre los investigadores de dos registros, a saber, el estudio sobre Resultados del Embarazo y Neonatales del Reino Unido y Globales en COVID‐19 (PAN‐COVID) y el Registro Nacional Perinatal de COVID‐19 de la Sección de Medicina Neonatal‐Perinatal (SONPM, por sus siglas en inglés) de la Academia Americana de Pediatría (AAP). Métodos: Se analizaron los datos del registro PAN‐COVID (del 1 de enero al 25 de julio de 2020), que incluye embarazos con sospecha de infección materna o confirmada por el SRAS‐CoV‐2 en cualquier fase del embarazo, y del Registro Nacional Perinatal COVID‐19 de la AAP‐SONPM (del 4 de abril al 8 de agosto de 2020), que incluye embarazos con resultados positivos de pruebas maternas para el SRAS‐CoV‐2 desde 14 días antes del parto hasta 3 días después del mismo. Los registros recolectaron datos sobre los resultados maternos, fetales, perinatales y neonatales. Los resultados de PAN‐COVID se presentan en conjunto para los embarazos con sospecha o confirmación de infección por el SRAS‐CoV‐2 y por separado en aquellos con infección confirmada. Resultados: Este estudio informa sobre 4.005 mujeres embarazadas con sospecha o confirmación de infección por SRAS‐CoV‐2 (1.606 de PAN‐COVID y 2.399 de AAP‐SONPM). En cuanto a los resultados obstétricos para PAN‐COVID en su conjunto y en aquellos con infección confirmada para PAN‐COVID y para AAP‐SONPM, respectivamente, se produjo la muerte materna en el 0, 5%, 0, 5% y 0, 2% de los casos, la muerte neonatal temprana en el 0, 2%, 0, 3% y 0, 3% de los casos y el éxitus fetal en el 0, 5%, 0, 6% y 0, 4% de los casos. El parto fue prematuro (<37 semanas de gestación) en el 12, 0% de todas las mujeres en PAN‐COVID, en el 16, 1% de las mujeres con infección confirmada en PAN‐COVID y en el 15, 7% de las mujeres en AAP‐SONPM. El parto prematuro extremo (<27 semanas de gestación) se produjo en el 0, 5% de los casos en PAN‐COVID y en el 0, 3% en AAP‐SONPM. La infección neonatal por SRAS‐CoV‐2 se notificó en el 0, 9% de todos los partos de PAN‐COVID, en el 2, 0% de los partos en los que se confirmó la infección en PAN‐COVID y en el 1, 8% en AAP‐SONPM; las proporciones de recién nacidos analizados fueron del 9, 5%, 20, 7% y 87, 2%, respectivamente. Las tasas de recién nacidos pequeños para la edad gestacional (PEG) fueron del 8, 2% en el total de PAN‐COVID, del 9, 7% de PAN‐COVID que tenían infección confirmada y del 9, 6% en AAP‐SONPM. Las puntuaciones Z medias del peso al nacer ajustadas a la edad gestacional fueron de −0, 03 en PAN‐COVID y de −0, 18 en AAP‐SONPM. Conclusiones: Los resultados de los registros del Reino Unido y de los Estados Unidos de embarazos con infección por el SRAS‐CoV‐2 concordaron de forma notable. Los partos prematuros afectaron a una proporción de mujeres mayor de la esperada, de acuerdo con los datos nacionales históricos y contemporáneos. Las proporciones de embarazos afectados por éxitus fetal, un bebé PEG o una muerte neonatal precoz fueron comparables a las de los datos históricos y contemporáneos del Reino Unido y de los Estados Unidos. Aunque la muerte materna fue infrecuente, la tasa fue más alta de lo esperado, de acuerdo con los datos de las poblaciones del Reino Unido y de los Estados Unidos, lo que probablemente se explique por la infravaloración de las mujeres afectadas por una infección más leve o asintomática en el embarazo en el estudio PAN‐COVID, aunque no en el estudio de la AAP‐SONPM. Los datos presentados apoyan fuertemente las recomendaciones sobre aumentar las precauciones para prevenir la infección por el SRAS‐CoV‐2 en el embarazo, en particular en relación a un mayor riesgo de parto prematuro y mortalidad materna, y sobre la vacunación prioritaria de las mujeres embarazadas y de las que planean un embarazo. Copyright © 2021 ISUOG. Published by John Wiley & Sons Ltd. 摘要: 患有COVID‐19的孕妇和新生儿的常见预后:来自PAN‐COVID以及AAP‐SONPM 注册中心的核心报道 摘要: 很少有大型队列研究报告有关妊娠期间与严重急性呼吸系统综合症冠状病毒2(SARS‐CoV‐2)感染相关的母亲，胎儿，围产期和新生儿预后的数据。 我们集结了来自两个注册中心(COVID‐19期间英国和全球孕妇和新生儿感染后预后研究中心(PAN‐COVID)及美国儿科学院新生儿&围产期医学部门的调查员研究(AAP)在大流行期间早期合作形成孕期感染的数据结果。 原理: 这是来自(2020年1月1日至7月25日)PAN‐COVID注册中心的数据份心，其中包括在怀孕任何阶段怀疑或确诊母亲SARS‐CoV‐2感染的病例，以及AAP‐SONPM国家围产期COVID‐19注册中心的数据分析(2020年4月4日至8月8日)，其中包括产前14天到产后3天对孕妇进行SARS‐CoV‐2检测阳性的案例。这些注册管理机构收集了有关孕产妇，胎儿，围产期和新生儿预后的数据。 这一PAN‐COVID注册中心的结果总体上显示了疑似或确诊SARS‐CoV‐2感染的孕妇，并将确诊者单独列分。 结果: 我们报告了4005名怀疑或确诊SARS‐CoV‐2感染的孕妇(1606例分析从PAN‐COVID中获取，而2399例AAP‐SONPM中获取)。对于产科的预后，整个PAN‐COVID中以及在AAP‐SONPM注册中心和PAN‐COVID注册中心确诊感染的孕妇中死亡率占0.5%，0.5%和0.2%，新生儿早期死亡分别占0.2%，0.3%和0.3%和死产占了0.5%，0.6%和0.4% 。在整个PAN‐COVID研究项目中，早产 (<37周妊娠)占所有女性的12%，其中在PAN‐COVID中心确诊的女性中有16.1%，在AAP‐SONPM中确诊女性占15.7%。 极度早产(妊娠<27周)发生在PAN‐COVID的比例是0.5%而AAP‐SONPM占了的0.3%。据报道，新生儿SARS‐CoV‐2感染占全部PAN‐COVID分娩总数的0.9%，确诊为PAN‐COVID感染的分娩孕妇占2.0%，AAP‐SONPM中则为1.8%；新生儿的检测率分别为9.5%，20.7%和87.2%。PAN‐COVID注册中心的小于胎龄新生儿(SGA)率为8.2%，他们中来自PAN‐COVID的有9.7%确诊感染，而来自AAP‐SONPM注册中心的感染率为9.6%。在PAN‐COVID注册中心，平均调整后胎龄的出生体重Z评分在PAN‐COVID为‐0.03，在AAP‐SONPM中为‐0.18。 结论: 来自英国和美国的SARS‐CoV‐2孕妇感染注册中心发现相当一致。根据历史和同期国家数据统计，早产对妇女的影响大于预期生产。受死产，小于胎龄儿(SGA)婴儿或新生儿早期死亡影响的怀孕比例与英国和美国历史与同期的数据具有可比性。尽管孕产妇死亡很少见，但根据英国和美国的人口数据该比率高于预期，这可能是由于在PAN‐COVID研究中症状较轻或是无症状携带者孕妇人数的不确定性造成的，尽管在SARS‐COV‐2注册中心并没有发现。 所提供的数据为加强预防SARS‐CoV‐2 措施，特别是在避免早产和产妇死亡风险增加以及建议孕妇和计划受孕的女性的优先接种疫苗方面，提供了强有力的指导，以加强预防孕妇感染SARS‐CoV‐2。 版权所有©2021 ISUOG。由John Wiley&Sons 有限公司发布。